DISPARITY OF THE ARABIC NAME: THE SPOTLIGHT ON CHILDREN OF ENDOGAMOUS AND EXOGAMOUS MARRIAGES AMONG HADRAMI-ARABS IN INDONESIA - Aribowo, Eric Kunto; Almasitoh, Ummu Hany (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
This study explores the influence of endogamous marriage (Arab-Arab family) and exogamous (Arab-Javanese family) on the personal name of Hadrami-Arab who living in the Kampong Arab Pasar Kliwon, Surakarta. Endogamous marriage among Hadrami-Arab resulted in identity retention, especially ethnic identity. In contrast, exogamous marriages play a role in generating a hybrid entity that inherits the characteristics of each ethnic parent, including personal name. Utilizing Net Consolidation Data for the First Semester of 2017 – download as of February 23, 2018– managed by the Data and Statistics Division of the Population and Civil Registration Agency of Surakarta, the names of the residents of Pasar Kliwon Subdistrict were classified according to the ethnicities of both parents. The elements in name construction were then identified to formulize the naming system utilizing the socio-onomastics framework. From the analysis, it can be revealed that the endogamous marriage became the dominant marriage as an effort to maintain the lineage of their ancestors, especially the male line (patrilineal). This effort is followed by giving the newborn baby name by adopting the name of his/her father, grandfather’s, or a combination of both. The attachment of surname after the personal name is also a characteristic of children who born from endogamous family. Meanwhile, families from exogamous marriages (Javanese mother and Arab fathers) prefer to name their child with a hybrid name through a combination of naming systems from their cultural background, Arabic-Javanese words and vise versa. The selection of Arabic names by Hadrami-Arabs is emphasized more highlight their ethnic identity, even though it also displays their religious status, Islam.